Comparison of the Fahn‐Tolosa‐Marin Clinical Rating Scale and the Essential Tremor Rating Assessment Scale. Issue 1 (23rd November 2017) - Ondo, William; Hashem, Vera; LeWitt, Peter A.; Pahwa, Rajesh; Shih, Ludy; Tarsy, Daniel; Zesiewicz, Theresa; Elble, Rodger
Abstract: Background: The Fahn‐Tolosa‐Marin Clinical Rating Scale for Tremor (FTM) has been used in large trials for essential tremor (ET), but its anchors for ratings from 0 to 4 of upper limb tremor are probably too low for patients with severe tremor (tremor amplitude >4 cm; grade 4). The Essential Tremor Rating Assessment Scale (TETRAS) is a validated clinical scale designed specifically for the assessment of ET severity. TETRAS has anchors that span a larger range of tremor amplitudes (>20 cm = grade 4), making it more suitable for assessing patients with severe ET. However, there is no direct comparison of these scales in any clinical trial. Methods: Upper limb postural and kinetic tremor items from both scales were compared using blinded, video‐recorded examinations of patients with moderate‐to‐severe ET who participated in a trial of focused ultrasound thalamotomy. Results: FTM ratings of postural and kinetic tremor correlated strongly with those of TETRAS. However, FTM exhibited a ceiling effect for severe tremor. Rest tremor, exclusive to FTM, correlated poorly with postural and kinetic tremor and had very poor test‐retest reliability. In contrast, wing‐beating postural tremor, exclusive to TETRAS, exhibited excellent test‐retest reliability and a strong correlation with kinetic and limbs‐extended‐forward postural tremor. Test‐retest reliabilities of the other TETRAS and FTM ratings were excellent, and both scales had good sensitivity to treatment effect. Conclusions: TETRAS has 2 main advantages over FTM in the assessment of tremor severity: (1) the absence of a ceiling effect in patients with severe ET, and (2) the inclusion of wing‐beating tremor.